PENGEMBANGAN POTENSI WISATA BUDAYA DI DUSUN SEMBAGEK DESA SUKADANA KECAMATAN BAYAN - Amril Watoni; mah Mahsun; I Wayan Suteja (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
The preparation of the thesis is based on the problem of how the strategy for developing potential cultural tourism destinations in Sembagek hamlet, Sukadana Village, Bayan District with the aim of researchers being able to get a strategy in developing cultural tourism in the Sembagek traditional hamlet in this study the researchers used descriptive qualitative methods. The data collected in this study were sourced from the results of interviews, observations and documentation from parties and institutions related to the development of tourist villages, namely cultural tourism from various data obtained by researchers collecting and processing data that had been obtained in the field for data analysis. data reduction, data presentation, and conclusion drawing. Of all the data that has been processed and analyzed, of course, get the results of the research. From the results of research in the field, it is known that the development of cultural tourism in the Sembagek hamlet requires infrastructure development in terms of attractions, amenities, accessibility, ancillary services, and institutions that have a positive impact on the economic empowerment of local communities. With the development carried out, people's incomes have increased, creating new business opportunities that have opened up job opportunities and fulfilled the needs of the population.